Trophic State of the Tajwid Lake, Langgam District, Pelalawan Regency, Riau Province Based on Trophic Index (TRIX) - Farida Sri Indah; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract There are several human activities such astourism and daily activities are conducted around the Tajwid Lake and thus the pollutant originated from those activities may enter the water and affects the trophic state of the lake. Trophic Index (TRIX) can be used to determine the trophic state of waters based on chemical and biological parameters. To understand the trophic state of the Tajwid Lake waters based on Vollenweider’s Trophic Index (TRIX), a research has been conducted in March-April 2018. There were three sampling points, namely in the inlet, in the middle of the lake, and in the end of the lake. In each sampling point, water was sampled from the surface (0.5 m) and 2 secchi depth (1.1 m). Sampling were conducted 3 times, once/week.Water quality parameters measured were DIN, total phosphorus, dissolved oxygen, chlorophyll-a, transparency, temperature, and pH. Result shown that the transparency was 0.47 - 0.55 m, temperature was 29.3 - 30.7 °C, pH was 5, DIN was 0.17 - 0.23 mg/L, total phosphorus was 0.32 - 0.62 mg/L, oxygen saturation was 59.37 - 82.77 % and chlorophyll-awas 6.03 - 10.71 µg/L.Trophic Index(TRIX) value of the Tajwid Lake was 4.39 - 5.49, and it indicates that the Tajwid Lake was eutrophic. Keywords : Kampar River, Vollenweider’s Trophic Index, Oxbow Lake, Eutrophic